2017
DOI: 10.18535/ijmsci/v4i12.09
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin Resistant Staphylococcus aureus in Pus samples

Abstract: Abstract:Methicillin Resistant Staphylococcus aureus (MRSA) is an emerging multidrug resistant bug worldwide. Knowing prevalence of MRSA is important to know for choosing empiric therapy and to screen colonized patients or staff. As Staphylococcus aureus is most common among pus samples, we have selected to do this study in this region. All clinical pus samples after receiving to Microbiology department, immediately inoculated in basal media such as Nutrient agar, Macconkey agar, Blood agar, Brain Heart Infusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…On comparison our present study with the previous study that have been done in different areas of the country. In similar to this study Devi U S et al 4 in 2017 there were 59 Staph aureus isolated 38 (64.4%) were males and 21 (35.5%) were females.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…On comparison our present study with the previous study that have been done in different areas of the country. In similar to this study Devi U S et al 4 in 2017 there were 59 Staph aureus isolated 38 (64.4%) were males and 21 (35.5%) were females.…”
Section: Discussionsupporting
confidence: 85%
“…MRSA were detected by their sensitivity to Cefoxitin/Oxacillin as performed according to CLSI guidelines. Prevalence of MRSA in previous study by Harshan K H et al, 11 Banker N et al 2 and Devi U et al 4 were 29.7%, 28.8% and 26.9%.A study of Banker N et al 2 showed only 1.9% isolates were resistance to Vancomycin. While in our study 2.5% isolated were resistance to Vancomycin.Harshan H K et al 11 in a study reported a high level resistance to Penicillin (97.5%), followed by Erythromycin (46.3%) and Gentamycin (29.7%).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation